Correlation and path coefficient analysis of top-cross and three-way cross hybrid maize populations - Sesay, S.; Ojo, D.K.; Ariyo, O.J.; Meseka, S.K.; Fayeun, L.S.; Omikunle, A.O.; Oyetunde, A.O. (Academic Journals, 2017)
Grain yield is a complex quantitative trait that depends on a number of other traits for selection. This study was carried out to reveal the pattern of association with and contribution of traits to grain yield in two maize populations evaluated in three agro-ecological zones of South-Western Nigeria during the 2014 cropping season. The experiment consisted of 10 top-cross and 10 three-way cross maize hybrids, laid out in a randomised complete block design with three replications. Genotypic and phenotypic correlation coefficients and path co-efficient analyses were performed for each hybrid population across the three locations. Results showed significant (p≤0.05) differences between the two hybrid populations for all the traits mentioned except days to 50% anthesis, ear diameter and 100-grain weight. Field weight in both hybrid populations, number of kernel rows per cob, ear diameter and ear height in top-cross hybrids, as well as ear length and 100-grain weight in the three-way cross hybrids were directly correlated with grain yield. The link between direct and indirect effects on grain yield depends on hybrid population, although some traits showed similar direct effects in both hybrid populations. These traits can be used as the main criteria for grain yield improvement in the respective hybrid populations.